Technical and tactical analysis of the nationwide championship matches in Greco-Roman and free wrestling style - Zylfi, S. (Science, Movement & Health, 2013)
Nationwide Championship Greco-Roman and free wrestling for youngsters was held 27-28 February 2010 Durres, Albania. The purpose of this study is to analyze the matches, examine the technical points for all participating teams in both styles. In the Greco-Roman style participated 6 teams, a total of 35 athletes, while the Free style was attended by 12 teams and in total 64 athletes. Method.The number of matches held in the Greco-Roman style was 42, where with 224 technical point of all participating teams; 22.32% of the points from the 50 kg weight category, 4.02% from 55 kg, 22.32% from 60 kg, 20.54% from 66 kg, 14.29% from 74 kg, 7.14% from 84 kg, 5.8% from 96 kg and 3.57% from 120 kg. 20 matches have ended with touch, 4 matches by technical superiority, 18 derived from the technical points derived from winners and losers. Results.The number of matches developed in the free style was 67, where 555 technical point of all participating teams were conducted; 9.55% of points from the 50 kg weight category, 11.17% from 55 kg, 12.25% from 60 kg, 23.78% from 66 kg, 26.13% from 74 kg, 7.39% from 84 kg, 3.06% from 96 kg and 6.67% from 120 kg. 31 matches have ended with the touch, 8 matches by technical superiority, and 28 matches with technical points derived from Winners and Losers. Conclusions.The study made it possible to analyze the performance of participating teams in both styles and gives recommendations for future improvements.